2020
DOI: 10.1097/mot.0000000000000771
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in precision medicine for individualized immunosuppression

Abstract: Purpose of review The current tools to proactively guide and individualize immunosuppression in solid organ transplantation are limited. Despite continued improvements in posttransplant outcomes, the adverse effects of over-immunosuppression or under-immunosuppression are common. The present review is intended to highlight recent advances in individualized immunosuppression. Recent findings There has been a great focus on genomic information to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…6 Several reviews have discussed the potential future role of ML in immunocompromised patients. [7][8][9][10][11][12] For example, ML-CDSSs have already been developed to predict patients at a risk of developing severe noninfectious posttransplant complications 13 such as assessing rejection in kidney transplant biopsies. 14 However, literature on antimicrobial stewardship based on ML in solid organ recipients is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…6 Several reviews have discussed the potential future role of ML in immunocompromised patients. [7][8][9][10][11][12] For example, ML-CDSSs have already been developed to predict patients at a risk of developing severe noninfectious posttransplant complications 13 such as assessing rejection in kidney transplant biopsies. 14 However, literature on antimicrobial stewardship based on ML in solid organ recipients is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] Recently, precision medicine that proposed the customization of diagnose and treatments has been considered as a strategy to overcome the issue of low efficacy, which could accomplish by decreasing the immunosuppression and resistance of cancers. [26] A large number of research results indicated that genetic heterogeneity and metabolic disorder of tumor are help for establishing complex immunosuppressive tumor microenvironment, which is the main cause of drug resistance in tumor. [27] These factors directly lead to the low accuracy and efficacy of traditional therapeutic strategies for anticancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Several excellent reviews have been published on machine learning in transplant medicine (3)(4)(5)(6). This review builds on prior knowledge by incorporating additional applications of machine learning in predicting acute post-surgical and longterm outcomes, caring for critically ill patients, classifying biopsy and radiographic data, augmenting pharmacologic decision making, and elucidating the complexity of host immune response.…”
Section: Introductionmentioning
confidence: 99%